The Influence of Green Accounting and Corporate Social Responsibility on Profitability with Corporate Governance as a Moderating Variable in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2022–2024 - Putri, Yeni Nor Diana; Hariyati, Hariyati; Wuryani, Eni; Triani, Ni Nyoman Alit; Nuswantara, Dian Anita; Pujiono, Pujiono (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the effect of Green Accounting and Corporate Social Responsibility (CSR) on profitability, with Corporate Governance as a moderating variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach using a saturated sampling technique involving 80 companies, resulting in 240 observations. Secondary data were obtained from annual reports, sustainability reports, and financial statements. Profitability was measured using Return on Assets (ROA), Green Accounting through environmental cost disclosures, CSR using the Global Reporting Initiative (GRI) G4 index, and Corporate Governance using the Corporate Governance Index (GCI). Data were analyzed using Moderated Regression Analysis (MRA). The results indicate that Green Accounting and Corporate Social Responsibility do not have a significant effect on profitability. Furthermore, Corporate Governance does not act as a moderating variable in the relationship between Green Accounting, CSR, and profitability. These findings suggest that sustainability practices and corporate governance mechanisms have not yet translated into direct financial performance outcomes during the study period.